Web GIS-Based Mapping of the Level of Damage to Houses Caused by Natural Disasters - Masruri, ruri; khurotul; fathul (Generation Journal, 2025)
Natural disasters can cause significant physical damage, especially to residential buildings. This study aims to develop a Web GIS-based mapping system for assessing the level of damage to houses caused by natural disasters in order to assist in the efficient identification and mitigation of post-disaster conditions. The research was conducted in Sridadi Village, Sirampog District, Brebes Regency, which is one of the areas prone to landslides. The damage assessment method uses scoring and weighting based on guidelines from the Ministry of Public Works and Public Housing, which covers building components such as foundations, columns, walls, and others. The system was built using the Django framework and PostgreSQL database. Testing was conducted using the Black Box method and User Acceptance Test (UAT). The test results showed that 91% of respondents stated that this Web GIS was very helpful for affected communities in determining the level of damage, and 78% stated that this system was useful for post-disaster planning and decision-making. These results prove that the Web GIS that was developed is effective in presenting spatial information and supporting the disaster recovery process